Local Government and Primary Health Care service delivery in South-Western Nigeria 2010–2015 - Peter Odion Irabor; Samuel Iheanacho Ebirim; Idowu Folorunso Aloba (Acta Politica Polonica, 2022)
Primary Health Care (PHC) is implemented by the local governments in Nigeria based on the notion that healthcare service delivery is efficient when it is closer to people. With the adoption of analytical research through secondary sources of data, this study assesses the local government performance in PHC service delivery and examines the challenges it faced in the south-western Nigeria states of Lagos, Ogun, and Ondo in the period of 2010–2015. The findings showed various PHC programmes implemented by the local governments of the selected states, which include Maternal and Child Reduction, Investment Case and Eko Free Malaria in Lagos state, Araya and Gbomoro in Ogun state, as well as the Mother and Child Hospitals and Agbebiye in Ondo state. However, findin gs showed similar challenges encountered by the local governments, which include multiplicity of stakeholders in the disbursement of PHC funds, lack of fiscal decentralisation of revenue to the local government, diversion of PHC funds as compared to other projects, and poor community participation in PHC, irregularity of or interference in the local government elections by the state government, exclusion and deviation from the key principles of PHC and lack of continuity in PHC programmes implemented. The general conclusion from the study is that the local government performance in PHC service delivery is weak. In order to enhance the present local government performance in PHC, the study recommends for the application and implementation of local government constitutional role in the management of the PHC service delivery.